Kraft pulp from juvenile and mature woods of corymbia citriodora - Severo, Elias Taylor Durgante [UNESP]; Sansígolo, Cláudio A. [UNESP]; Calonego, Fred W. [UNESP]; Barreiros, Ricardo Marques [UNESP] (My University, 2013)
Kraft pulp produced from juvenile and mature wood from thirty-two-year-old Corymbia citriodora trees was evaluated. The stem was subdivided into regions of juvenile and mature wood, and then it was transformed into chips. These materials were then cooked in the Laboratory of Pulp and Paper at São Paulo State University (UNESP, Botucatu, SP, Brazil) and the physico-mechanical properties of the pulps were determined. The results showed that: (1) the pulp yields of mature wood were up to 4.4% greater in comparison to the juvenile wood, (2) the juvenile wood pulp required a shorter refining time than mature wood to reach the same Schopper-Riegler degree, (3) the juvenile wood pulp presented lower specific volume, and (4) the mature wood pulp presented greater air resistance, tensile, tear and burst index values, stress-strain factor, and stretch than the juvenile wood pulp.
Keywords: Corymbia citriodora; Juvenile wood; Kraft pulps; Mature wood; Pulp properties; Air resistance; Corymbia; Juvenile woods; Physicomechanical properties; Pulp and paper; Stress-strain; Kraft pulp; Mechanical properties; Pulp materials; Pulp refining; Wood; Juvenile Wood; Kraft Pulps; Mature Wood; Mechanical Properties